Portion of Married Daughters in Inheritance Share among Angkola Batak Community - Ritonga, Raja; Harahap, Sumper Mulia; Asrul Hamid; Andri Muda; Zuhdi Hsb (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2024)
It is believed that Islamic law provides a fair share for inheritance among men and women or among sons and daughters. However, it does not always happen that way like what occurs in Angola Batak community with Muslims as its majority at the South Tapanuli. This article focuses on married daughters’ gain in inheritance share. The problems discussed are: First, what are the types of married daughters’ inheritance gain in Angkola Batak’s customs? Second, what are triggering factors beyond the types of married daughters’ inheritance gain? Third, how does the sharing practice imply to the Islamic law? This field research relies on primary data obtained from both observation and interviews. Research informants were selected based on relevance criteria to the research subject, Angkola Batak women who get the inheritance share from their birth families and some relevant parties. Additionally, it also used secondary data from a literature study employing a sociological approach to reveal the reality vividly. The interpretative data analysis was through several stages starting from data collection and reduction and then drawing conclusions. It reveals four types of married daughters’ share in inheritance: (1) in contrast to the share of sons, (2) the share is collectively distributed among fellow sisters, (3) the share is temporary, and (4) no inheritance gain at all. Second, the four types stem from both socially constructed considerations as well as divinely given factors. Third, the share implies either improvisation, deviance, as well as local values embed in Islamic law.